Effect of Abiotic Climatic Factors on the Gonadal Maturation of the Biocontrol Agent Sphaerophoria rueppellii (Wiedemann, 1830) (Diptera: Syrphidae) - José J. Orengo-Green; José L. Casas; Mª. Ángeles Marcos-García (Insects, 2022)
The hoverfly Sphaerophoria rueppellii is currently one of the most effective predators commercially available for aphid pest control. However, knowledge of the reproductive system of males and females of this syrphid is limited. The present article aims to report how changes in the temperature and photoperiod may affect development of the gonads (ovaries and testes), oviposition, and fecundity during the lifespan of S. rueppellii. Four environmental conditions (14L:10D, T: 20 ± 1 °C; 12L:12D, T: 20 ± 1 °C; 14L:10D, T: 25 ± 1 °C; and 12L:12D, T: 25 ± 1 °C) were used to determine oviposition, hatching percentage, and lifespan during a period of 30 days after the adult emergence. The maturation of the ovaries was done under three treatments (barley leaves with aphids always available; barley leaves two days per week with aphids available; no barley leaves available), and in the same environmental conditions noted above. Males at 14L:10D, 20 ± 1 °C; and 14L:10D, 25 ± 1 °C; were used to analyze and study the maturation of the testes. Females at 14L:10D; T: 25 ± 1 °C showed a significant difference in oviposition, percentage of hatching, and rate of eggs. A detailed description of the male and female gonads was undertaken, and it was determined that the conditions in which males sexually mature early are at 14L:10D, 25 ± 1 °C. These results will improve the application of S. rueppellii in crops, for the control of aphid pests.